Optimization of micro-EDM drilling of inconel 718 superalloy - Ay, Mustafa; Caydas, Ulas; Hascalik, Ahmet (Springer London Ltd, 2013)
In this study, the gray relational analysis method was used to optimize the micro-electrical discharge machining (EDM) drilling process of Inconel 718 nickel-based superalloy with multiperformance characteristics. In order to determine the best factor level conditions, a full factorial experimentation was performed based on the micro-EDM parameters of discharge current and pulse duration. The hole taper ratio (H (t)) and hole dilation (H (d)) were the measured performances. By analyzing the used optimization results, it was observed that the pulse current was more efficient on performance characteristics than pulse duration. The characteristics of drilled surfaces and tool electrodes were also investigated by using optical and scanning electron microscopy. A linear regression model was developed to estimate the performances. The measured and model results were in a good agreement with correlation coefficients of R (2) = 0.897 and R (2) = 0.929 for H (t) and H (d), respectively. It is concluded that the EDMed hole quality can be improved effectively through this approach.
Keywords: Gray relational analysis; Micro-EDM; Inconel 718